Middle East and Central Asia : A Survey of Gender Budgeting Efforts - Kolovich, Lisa (IMF Working Papers; Working Paper ;, 2016)
Gender budgeting uses fiscal policies to promote gender equality and women's advancement, but is struggling to take hold in the Middle East and Central Asia. We provide an overview of two gender budgeting efforts in the region-Morocco and Afghanistan. Achievements in these two countries include increasing female primary and secondary education enrollment rates and reducing maternal mortality. But the region not only needs to use fiscal policies for women's advancement, but also reform tax and financial laws, enforce laws that assure women's safety in public, and change laws that prevent women from taking advantage of employment opportunities.